Turning the promise of multipurpose prevention technologies into a market reality: a commentary - Dam, Anita; Schueller, Jane; Peine, Kevin J.; Mason, Jennifer; Dorward, Emily; Vij, Ashley (Frontiers in Reproductive Health, 2023)
The promise of multipurpose prevention technologies (MPTs) for the prevention of HIV and unintended pregnancy are on the horizon. While many are still in clinical development, others are closer to becoming a realistic, accessible option for users, like the dual prevention pill (DPP). Researchers, governments, donors, and implementers will have to collaboratively address systemic challenges to successfully introduce and scale-up MPTs. To ensure the rollout of MPTs is successful, the global community should address user and country-specific needs, coordinate with advocates and policymakers, and set a realistic plan for product introduction and scale-up that considers the needs of both family planning (FP) and HIV programs, while laying the groundwork for future new product introduction. To achieve these aims, global and regional stakeholder coordination should emphasize country-led, person-centered decision-making while addressing: (1) procurement and supply chain barriers; (2) the potential burden on health systems; and (3) the impact on current programs.